Functional toll-like receptor 4 links endotoxin sensing to platelet priming in feline platelets - Li, Ronald H. L.; Shaverdian, Meg; Chen, Cheyenne; Stuhlmann, Claire; Stern, Joshua A.; Nguyen, Nghi (Frontiers in Veterinary Science, 2026)
ObjectiveTo characterize toll-like receptor 4 (TLR4) expression in feline platelets and to assess the priming potential of Escherichia coli lipopolysaccharide (LPS) in the presence or absence of physiologic agonists. In addition, the downstream effects of TLR4 activation on arachidonic acid (AA)-mediated signaling were investigated.MethodsEighteen healthy staff- and student-owned cats were enrolled. Washed platelets prepared from whole blood were analyzed for total and surface TLR4 expression using Western blotting, flow cytometry, and super-resolution immunofluorescence microscopy in the presence or absence of stimulation. The priming potential of LPS was evaluated by measuring alpha-granule secretion by P-selectin expression and thromboxane B2 (TxB2) generation, as a surrogate of TxA2, in response to adenosine diphosphate (ADP) or AA using flow cytometry and ELISA, respectively. To further examine TLR4-dependent signaling, phosphorylation of vasodilator-stimulated phosphoprotein (P-VASP) was quantified following stimulation with AA and LPS from Rhodobacter sphaeroides (LPS-RS).ResultsThrombin stimulation significantly upregulated both surface and total platelet TLR4 expression. While LPS alone did not induce α-granule secretion with or without ADP, it reversed the inhibitory effect of AA by enhancing P-selectin expression and potentiating TxB2 generation. This priming effect of LPS was mediated through TLR4, resulting in decreased cytoplasmic P-VASP, a marker associated with platelet inhibition.DiscussionThis study is the first to demonstrate functional TLR4 expression in feline platelets. Activation of TLR4 sensitizes platelets to AA by augmenting TxA2 production and attenuating prostaglandin-dependent inhibitory pathways. These findings highlight a novel mechanism by which platelet TLR4 contributes to immunothrombosis and may promote thrombotic risk in cats.